Morfologi Mutan Alfalfa (Medicago sativa L.) Hasil Iradiasi Sinar Gamma Pada Cekaman Kering: Mutant Morphology of Alfalfa (Medicago sativa L) Result of Gamma Ray Irradiation in Dry Stress - Desima Natalia Harianja; P D M H Karti; I Prihantoro (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2021)
Alfalfa in dry stress conditions cannot grow optimally. Drought inhibits growth and reduces alfalfa production in many cultivation systems. Plants breeding with gamma-ray irradiation and in vitro selection using PEG found somaclonal variants adapted to grow well in drought conditions. This study aims to determine the type of mutation with the best morphology in dry stress conditions. Alfalfa mutants resulting from gamma irradiation were sub-cultured in vitro. Alfalfa mutants cultured in PEG medium, according to treatments. This experiment used completely randomized factorial design with 2 factors, namely the gamma-ray irradiation doses (0 Gy, 100 Gy, 200 Gy, 300 Gy, 400 and 500 Gy), and PEG concentrations (5%, 10%, 15%, and 20% ). The variables observed were viability, plant height, number of leaves, wet weight, medium shrinkage, leaf wilting, and leaf color. The results showed that the gamma-irradiated mutant had a better (p<0.05) morphology than the control (0 Gy) in the face of dry stress conditions. Combination of 500 Gy and 20% PEG concentration resulted the best type of mutant. Key words: alfalfa, in vitro, gamma rays, PEG